New records of epilachnine lady-beetles (Coleoptera, Coccinellidae, Coccinellinae) of Peru - Bustamante-Navarrete, Abdhiel Arnaldo (2018)
The phytophagous coccinellids Toxotoma guerini Gordon 1975 and Epilachna bistriguttata Mulsant 1850 are species previously known only from Bolivia and Ecuador. Here, they are reported for the first time in Peru, in the regions of Cusco and Puno. The female of both species, unknown until now, is described and illustrated. In addition, an updated distribution map of both species is presented.